The effect of plant-derived dietary protein sources on cultured abalone Haliotis midae (L. 1758) digestive physiology - Wright, Jason Geoffrey (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
The growth and feed conversion ratio of farmed abalone Haliotis midae (L. 1758) fed a formulated diet varies in feeds with different protein sources. To better understand this, the effect that various combinations of dietary soybean meal (SBM), sunflower meal (SFM) and fishmeal (FM) had on the digestive efficiency of farmed H. midae when included in a formulated feed, were assessed. The aim of this study was to investigate the effect that plant-based proteins had on abalone digestion and gut-bacterial profile of cultured adult abalone when combined with fishmeal. This was done by analysing the chymotrypsin (protease) and cellulase (carbohydrase) digestive enzyme activities from whole-gut sections of farmed abalone that were fed one of four diets for 12 months: FM-only, SBM-only, fishmeal and soybean meal (FM-SBM), and fishmeal and sunflower meal (FM-SFM). There were significant interactions between the diets, sampling date, and sex of the abalone, which had an influence on the cellulase activities in the digestive tracts of the animals. Those fed the SBM diet had the highest cellulase activity by the end of the sampling period (ANOVA; df = 9; F = 2.9; P = 0.005). The significant interactions between diet and sampling date influenced the chymotrypsin activities of abalone. Animals fed the FM diet had the highest activity of chymotrypsin for most of the sampling period (ANOVA; df = 9; F = 2.5; P = 0.01). Therefore, diet did have an impact on the cellulase and chymotrypsin activities of abalone fed either combination diets (FM-SBM; FM-SFM) or single protein diets (FM; SBM). The presence of plant material such as cellulose fibres in the diets containing plant proteins may have influenced the cellulase activity levels of each treatment as it would have stimulated endogenous and exogenous cellulase production. However, treatments with the highest crude fibre content, SBM and FM-SFM, resulted in differing activities. The activity levels of chymotrypsin may have been impacted by the protein type, presence of protein inhibitors and temporal changes in utilisation. Abalone fed the FM diet exhibited the highest chymotrypsin activities on sampling day 182, which was in summer. Animals fed the treatment diets containing fishmeal also developed their reproductive tissues, and may explain the low chymotrypsin activities in abalone fed SBM-only. Additionally, the presence of allergenic compounds would have influenced enzyme activity, as they would have negatively affected the nutrient utilisation and absorptive capacity. Fluctuations in water temperature may have had an effect on enzyme activity, as activities were highest during summer, when seawater temperatures are most variable. A change to lowered water temperatures are known to trigger the growth of digestive epithelial tissue in abalone to allow for increased enzyme secretions and nutrient absorption (Schaeffer et al. 2013). The effect that plant protein inclusion in abalone diets had on the gut-microbiota was revealed by analysing the differences in gut-bacterial community profiles, through the use of metagenomic sequencing. The relative abundance of the phylum Verrucomicrobia, class Verrcomicrobiae and the genus Rubritalea were highest in the SBM diet. These bacterial groups were also influenced by the plant material from soybean meal, as hydrolysed cellulose is broken down by cellulases, and allowed for the proliferation of Rubritalea bacteria due to them using cellobiose as an energy source. The presence of Bacteroidetes was due to the phyla having bacterial species that can breakdown proteins and species that can break down carbohydrates. The animal protein present in the composition of the FM diet had a positive influence on proteolytic Bacteroidetes growth. The high levels of cellulose from the plant fibres in the soybean meal-only diet (SBM) promoted growth of saccharolytic Bacteroidetes. Tenericutes bacteria's prominence was due to the higher plant fibres from the soybean meal as some Mycoplasma are known to degrade polysaccharides. Therefore, exposure to formulated feeds with high levels of these plant materials would allow for high proliferation. The thesis established that plant-derived dietary proteins in formulated feeds result in an effect on digestive enzyme activity and a difference in the community structure of gut bacteria in H. midae abalone. The results from the current research highlight the importance of studying abalone gut physiology when investigating the impacts of formulated feed composition, and can be used as an additional factor when determining the efficacy of a dietary component. Further research on the gut-bacterial groups and different digestive enzymes of H. midae abalone is encouraged, in order to create a holistic view on their response to dietary plant proteins inclusion in formulated feeds, thus reducing the need for fishmeal protein.
Keywords: Haliotis midae -- South Africa; Haliotis midae -- Nutrition -- South Africa; Haliotis midae -- Physiology -- South Africa; Haliotis midae -- South Africa -- Growth; Haliotis midae -- Digestive organs; Abalone culture -- South Africa; Plant proteins as feed